Possible mechanisms of SARS-CoV-2-associated myocardial fibrosis: reflections in the post-pandemic era - Wang, Zhan; Li, Luwei; Yang, Shuai; Li, Zhengrui; Zhang, Pengpeng; Shi, Run; Zhou, Xing; Tang, Xiaojuan; Li, Qi (Frontiers in Microbiology, 2024)
Since December 2019, coronavirus disease 2019 (COVID-19) has been spreading worldwide with devastating immediate or long-term effects on people’s health. Although the lungs are the primary organ affected by COVID-19, individuals infected with SARS-CoV-2 also develop systemic lesions involving multiple organs throughout the body, such as the cardiovascular system. Emerging evidence reveals that COVID-19 could generate myocardial fibrosis, termed “COVID-19-associated myocardial fibrosis.” It can result from the activation of fibroblasts via the renin-angiotensin-aldosterone system (RAAS), transforming growth factor-β1 (TGF-β1), microRNAs, and other pathways, and can also occur in other cellular interactions with SARS-CoV-2, such as immunocytes, endothelial cells. Nonetheless, to gain a more profound insight into the natural progression of COVID-19-related myocardial fibrosis, additional investigations are necessary. This review delves into the underlying mechanisms contributing to COVID-19-associated myocardial fibrosis while also examining the antifibrotic potential of current COVID-19 treatments, thereby offering guidance for future clinical trials of these medications. Ultimately, we propose future research directions for COVID-19-associated myocardial fibrosis in the post-COVID-19 era, such as artificial intelligence (AI) telemedicine. We also recommend that relevant tests be added to the follow-up of COVID-19 patients to detect myocardial fibrosis promptly.